"What Do I Call You?" Postcolonial Pastoral Care and Counseling: Ambiguous Sense of Self with Perspectives on the Experience of Korean Clergywomen. Issue 1 (2nd January 2017) - Lee, Ahyun
Abstract : This research explores the ambiguous sense of self with the complexity of the psychological experiences of racial–ethnic minority women, especially Korean immigrant women's subordinate roles in intercultural contexts. Through critical analysis of subjective experiences, this study addresses pastoral theological reflection with the ambiguous sense of self through the lens of postcolonial theology. The research method of intuitive inquiry through qualitative case study research was used in order to share the subjective experiences of five interviewees ( O, H, J, M, and S), constituting both a Samo (a pastor's wife) in Korean immigrant churches and a Moksa (a pastor) in cross-cultural and cross-racial appointments in the United Methodist Church in the United States. Using the interviewees' narratives of being a Moksa and/or Samo, this research addresses multi-oppressions affecting Korean clergywomen working within immigrant contexts. In light of these findings, future research on the psychological influences on Korean clergywomen might consider exploring how a pastoral caregiver can respond clinically to their subordination and the gender and racial oppression they experience in their ministries and in their everyday lives.